Development of a simple exoskeleton (hardware) - Mohd Yashim, Wong Paul Tze (2013)
The Powered Exoskeleton is an electromechanical structure worn by an operator, matching the shape and functions of the human body. Exoskeletons supplements the function of the human limb by augmenting its strength, agility and endurance or at least by supplying the activation energy required to initiate the limb's movements. This project provides the detailed steps on the design of powered exoskeleton structures and considerations involved when designing it. Considerations such as ergonomics, loadings and actuator capabilities,costs and manufacturability were taken into consideration during the early steps. To be kinematically compatible with human walking motion, gait analysis or the study of human walking have been performed. Kinovea which is a video motion analysis was used to capture all the walking data. For actuation, two actuators; Pneumatic Muscle Actuator and Pneumatic Cylinders were tested for compliant actuation. Solidworks is used to design the frame and to perform Finite Element Analysis as well as a motion simulator to check compatibility with human motion. All data were compared taking actual gait data as benchmark.